Use of mesocosm and field studies to assess the effects of nutrient levels on phytoplankton population dynamics in Korean coastal waters - Yoon, Ji Nam; Lim, Young Kyun; Hong, Seongjin; Baek, Seung Ho (Frontiers in Marine Science, 2024)
We integrated data from field observations during April and March with data from a 2-week mesocosm experiment to investigate changes in phytoplankton populations in southern Korean coastal waters (KCWs) following nutrient enrichment during early spring of 2021. The mesocosm experiments used 1000 L cylindrical plastic containers that had natural seawater (control), a low nutrient (LN) treatment, or a high nutrient (HN) treatment. The field observations showed that increased freshwater runoff following spring rainfall led to elevated levels of dissolved inorganic nitrogen and silicate and a significant increase in total phytoplankton abundance. In March, nutrient enrichment from water mixing and terrestrial runoff led to dominance of cryptophyte Cryptomonas spp.. In April, higher nutrient levels than March (p < 0.05) resulting from increased terrestrial runoff after rainfall and dominant species were Skeletonema spp., and Cryptomonas spp.. In the mesocosm experiment, a succession from E. zodiacus initially to Chaetoceros spp. in the middle stage, and then to Cylindrotheca closterium and Pseudo-nitzschia spp. finally was observed, depending on the species-specific nutrient availability after nutrient addition. In principal component analysis, the negative correlation between C. closterium and nutrient levels supports their nutrient availability, which is an adaptation to low-nutrient conditions. The combined data from the field observations and mesocosm experiments indicated that nutrient supplementation from terrestrial runoff and tidal mixing played a crucial role in determining the dynamics of phytoplankton populations during early spring in the KCWs.